INVESTIGATING DETERMINANTS OF POST-TRAUMATIC STRESS SYMPTOMS: PSYCHOLOGICAL, PHYSIOLOGICAL, AND PERSONALITY INFLUENCES PRE- AND POST-TRAUMA - Dr. Mote Srikanth (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This study explored pre-trauma psychological and physiological factors associated with post-traumatic stress symptoms (PTSS) in firefighters and police officers. A total of 91 participants underwent pre-trauma psychometric, diagnostic, and psychophysiological assessments, followed by post-trauma evaluations. Key pre-trauma predictors of elevated PTSS included lower cognitive ability (IQ), depressive symptoms, and heightened physiological responses during fear conditioning. Differential corrugator EMG responses and skin conductance (SC) reactivity significantly correlated with PTSS severity. Logistic regression analysis identified lower IQ, higher depression scores, and greater EMG responses as significant predictors of post-trauma IES-R scores. Additionally, increased SC responses predicted higher posterior probability scores. Despite mild PTSS severity, the findings underscore the importance of pre-trauma factors in predicting PTSS outcomes. The study highlights the need for early identification tools to support individuals at risk of developing PTSS or PTSD. Future research should involve larger samples, extended follow-up periods, and high-risk populations to enhance understanding of pre-trauma risk markers.